2020
DOI: 10.1093/biolinnean/blz209
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical structure of the pygmy shrew: revisiting the roles of southern and northern refugia in Europe

Abstract: Southern and northern glacial refugia are considered paradigms that explain the complex phylogeographical patterns and processes of European biota. Here, we provide a revisited statistical phylogeographical analysis of the pygmy shrew Sorex minutus Linnaeus, 1766 (Eulipotyphla, Soricidae), examining its genetic diversity, genetic differentiation and demographic history in the Mediterranean peninsulas and in Western and Central Europe. The results showed support for genetically distinct and diverse phylogeograp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
(43 reference statements)
0
9
0
1
Order By: Relevance
“…Species, which are common in the Caucasus Mountains are also absent in mountainous Crimea (voles of the Terricola subgenus, and the dormice Dryomys nitedula Pallas, 1778 and Glis glis Linnaeus, 1766). However, the Caucasian pygmy shrew Sorex volnuchini has recently been found in Crimea ( Vega et al 2020 ) but we have no information on this species in the current study.…”
Section: Introductionmentioning
confidence: 85%
“…Species, which are common in the Caucasus Mountains are also absent in mountainous Crimea (voles of the Terricola subgenus, and the dormice Dryomys nitedula Pallas, 1778 and Glis glis Linnaeus, 1766). However, the Caucasian pygmy shrew Sorex volnuchini has recently been found in Crimea ( Vega et al 2020 ) but we have no information on this species in the current study.…”
Section: Introductionmentioning
confidence: 85%
“…In Europe, several overarching patterns have emerged from fossil data and phylogeographic studies, with refugia identified in the three “classic” Mediterranean (Iberian, Apennine and Balkan) peninsulas (Hewitt, 1999; Sommer & Nadachowski, 2006; Taberlet et al, 1998), but also further north in areas in or adjacent to the Carpathians mountains and the Dordogne region in France as examples of “cryptic refugia” (McDevitt et al, 2012; Provan & Bennett, 2008; Stojak et al, 2016). Phylogeographic studies of the most widely studied group, the terrestrial mammals, have shown distinct mitochondrial DNA (mtDNA) lineages in small mammals (Searle et al, 2009; Stojak et al, 2016; Vega et al, 2020) and ungulates (Carden et al, 2012; Sommer et al, 2008) that are consistent with contraction and re‐expansion from these refugial regions (Hewitt, 1999; Taberlet et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogeographic studies of the most widely studied group, the terrestrial mammals, have shown distinct mitochondrial DNA (mtDNA) lineages in small mammals (Searle et al, 2009;Stojak et al, 2016;Vega et al, 2020) and ungulates (Carden et al, 2012;Sommer et al, 2008) that are consistent with contraction and re-expansion from these refugial regions (Hewitt, 1999;Taberlet et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Su capacidad de dispersión relativamente limitada, tiempo de generación corto y asociaciones estrechas con hábitats particulares, han contribuido a que las musarañas reciban una atención especial para evaluar el papel que han jugado el cambio climático del pasado y la orografía en la conformación de los patrones de variabilidad genética actual y los procesos de divergencia de linajes. Lo anterior ha sido particularmente importante en regiones templadas, boreales y paleotropicales (Giarla y Esselstyn, 2015;Hope et al, 2020;Jacquet et al, 2013;Vega et al, 2020;Vuilleumier y Fontanillas, 2007). En el Neotrópico, la situación es diferente.…”
Section: Introductionunclassified